Diagnostic thoracoscopy in undiagnosed pleural effusion: Our experience in Manmohan cardio-thoracic vascular and transplant Center - Shrestha, Uttam Krishna; Thapa, Bibhusal; Sayami, Prakash (Journal of General Practice and Emergency Medicine of Nepal, 2014)
Introduction: Diagnosis of exudative pleural effusions can often be elusive leading to delayed or misdirected treatment. Pleural biopsy remains the gold standard in the diagnosis but blind biopsy have historically low yields while thoracoscopic biopsies give ≥90% results. We reviewed our experience with thoracoscopic pleural biopsy.Methods: A retrospective observational study of patients with exudative pleural effusions which had Adenosinedeaminase (ADA) values ≤ 60 and ≥ three cytology samples negative for malignancy was conducted. These patients were subjected to thoracoscopy and pleural biopsy. The concordance of pre and post operative diagnosis and morbidity of the procedure were studied.Results: Seventeen such patients with mean age of 39.3±19.8 years (11 to 70 years) and Male to Female ratio of 10:7 underwent thoracoscopic pleural biopsy between Jan 2012 – Jan 2013. The average duration of effusion was 11.05 ±2.34weeks. Seven patients had either taken or were currently on a course of antitubercular treatment at the time of pleural biopsy. The presumptive clinical diagnosis was tuberculosis in nine patients, malignancy in three and unsure in five. The final histopathology confirmed pleural tuberculosis in only two while metastatic adenocarcinoma was found in six patients and non-specific pleural inflammation in nine. Pleurodesis was done in six and decortication in five patients.Conclusion: Thoracoscopy should be considered when the cause of pleural effusion is elusive. Judicious use of this diagnostic modality may avoid delayed or misdirected treatment in people with pleural effusions and also offer opportunity of therapeutic intervention when needed.